Kualitas Susu Kuda Sumbawapada Penyimpanan Suhu Ruang - Sinlae, Reny Navtalia; Suada, I Ketut; Sampurna, I Putu (Buletin Veteriner Udayana, 2017)
Research has been conducted to determine the quality of Sumbawa horse milk at room temperature storage. Each sample (of 5 horse) was divided into 5 cups Beaker and then stored at room temperature. Observations were made as many as 6 times to checked and tested on parameters including pH, alcohol, smell and a flavor test. This study uses a randomized block design (RBD), using 5 horses as a group, and time observations on days 0, 1 st , 2 nd , 3 rd , 4 th , and 5 th as a treatment, so tested 30 samples. The results showed that the pH of milk has significantly (P>0,05) lower quality. On the alcohol test showed positive results and the test on the smell and flavor test shaved changes quality after the 2 nd day. Of observations Sumbawa horse milk quality decrease very markedly decreased pH (P<0.01) on day 0 to day 1 and significantly (P<0.05) decreased from day 1 to day 2 but not significant (P>0.05) decreased from day 2 to day 3 during storage. Alcohol test resistance at Sumbawa horse milk increasingly distorted and react positively. On the smell and flavor test Sumbawa horse milk taste very significant (P<0.01) deviates smells during storage at room temperature begins 2 nd day. To maintain the quality of Sumbawa horse milk should be stored no more than 2 days at room.